Natural rubber materials. Volume I, - Thomas, Sabu (RSC polymer chemistry series ;, 2014)
The combination of its unique morphology, physical properties, cost effectiveness and environmental friendliness make natural rubber an appealing constituent for many materials and applications. This comprehensive two volume set covers the synthesis, characterization and applications of natural rubber based blends, interpenetrating polymer networks, composites and nanocomposites. Volume 1 covers different types of natural rubber-based blends and IPNs as well as manufacturing methods, thermo mechanical characterization techniques, life cycle analysis and their applications. Volume 2 focuses on.